Microwave Induced One-pot Stereoselective Synthesis of Alkyl Z-2-[2-amino-4-oxo-1,3-selenazol-5(4H)-yliden)acetates in Solvent-less Conditions - Ramazani, Ali; Ahmadi, Ebrahim; Ganjeie, Bijan; Reza Kazemizadeh, Ali; Morsali, Ali (Asian Journal of Chemistry, 2016)
Selenourea reacts with dialkyl acetylenedicarboxylates in solvent-less conditions to form 1 : 1 adducts, which undergo a cyclization reaction to produce alkyl Z-2-(2-amino-4-oxo-1,3-selenazol-5(4H)-yliden)acetates under microwave irradiation and also under thermal conditions in solvent-less system in fairly good yields. Stereochemistry of the ethyl Z-2-(2-amino-4-oxo-1,3-selenazol-5(4H)-yliden)acetate was established with using of X-ray single crystal structure analysis. The reaction is completely stereoselective.